Structural analysis of glycans and development of microarrays from Helcobacter pylori cell surface glycome - Silva, Lisete Machado e (2014)
Helicobacter pylori is a bacterial pathogen that affects more than half of the world’s population with gastro-intestinal diseases and is associated with gastric cancer. The cell surface of H. pylori is decorated with lipopolysaccharides (LPSs) composed of three distinct regions: a variable polysaccharide moiety (O-chain), a structurally conserved core oligosaccharide, and a lipid A region that anchors the LPS to the cell membrane. The O-chain of H. pylori LPS, exhibits unique oligosaccharide structures, such as Lewis (Le) antigens, similar to those present in the gastric mucosa and are involved in interactions with the host. Glucan, heptoglycan, and riban domains are present in the outer core region of some H. pylori LPSs. Amylose-like glycans and mannans are also constituents of some H. pylori strains, possibly co-expressed with LPSs. The complexity of H. pylori LPSs has hampered the establishment of accurate structure-function relationships in interactions with the host, and the design of carbohydrate-based therapeutics, such as vaccines. Carbohydrate microarrays are recent powerful and sensitive tools for studying carbohydrate antigens and, since their emergence, are providing insights into the function of carbohydrates and their involvement in pathogen-host interactions. The major goals of this thesis were the structural analysis of LPSs from H. pylori strains isolated from gastric biopsies of symptomatic Portuguese patients and the construction of a novel pathogen carbohydrate microarray of these LPSs (H. pylori LPS microarray) for interaction studies with proteins. LPSs were extracted from the cell surface of five H. pylori clinical isolates and one NCTC strain (26695) by phenol/water method, fractionated by size exclusion chromatography and analysed by gas chromatography coupled to mass spectrometry. The oligosaccharides released after mild acid treatment of the LPS were analysed by electrospray mass spectrometry. In addition to the conserved core oligosaccharide moieties, structural analyses revealed the presence of type-2 Lex and Ley antigens and N-acetyllactosamine (LacNAc) sequences, typically found in H. pylori strains. Also, the presence of O-6 linked glucose residues, particularly in LPSs from strains 2191 and NCTC 26695, pointed out to the expression of a 6-glucan. Other structural domains, namely ribans, composed of O-2 linked ribofuranose residues were observed in the LPS of most of H. pylori clinical isolates. For the LPS from strain 14382, large amounts of O-3 linked galactose units, pointing to the occurrence of a galactan, a domain recently identified in the LPS of another H. pylori strain. A particular feature to the LPSs from strains 2191 and CI-117 was the detection of large amounts of O-4 linked N-acetylglucosamine (GlcNAc) residues, suggesting the presence of chitin-like glycans, which to our knowledge have not been described for H. pylori strains. For the construction of the H. pylori LPS microarray, the structurally analysed LPSs, as well as LPS-derived oligosaccharide fractions, prepared as neoglycolipid (NGL) probes were noncovalently immobilized onto nitrocellulosecoated glass slides. These were printed together with NGLs of selected sequence defined oligosaccharides, bacterial LPSs and polysaccharides. The H. pylori LPS microarray was probed for recognition with carbohydratebinding proteins (CBPs) of known specificity. These included Le and blood group-related monoclonal antibodies (mAbs), plant lectins, a carbohydratebinding module (CBM) and the mammalian immune receptors DC-SIGN and Dectin-1. The analysis of these CBPs provided new information that complemented the structural analyses and was valuable in the quality control of the constructed microarray. Microarray analysis revealed the occurrence of type-2 Lex and Ley, but not type-1 Lea or Leb antigens, supporting the results obtained in the structural analysis. Furthermore, the H. pylori LPSs were recognised by DC-SIGN, a mammalian lectin known to interact with this bacterium through fucosylated Le epitopes expressed in its LPSs. The -fucose-specific lectin UEA-I, showed restricted binding to probes containing type-2 blood group H sequence and to the LPSs from strains CI-117 and 14382. The presence of H-type-2, as well Htype- 1 in the LPSs from these strains, was confirmed using specific mAbs. Although H-type-1 determinant has been reported for H. pylori LPSs, this is the first report of the presence of H-type-2 determinant. Microarray analysis also revealed that plant lectins known to bind 4-linked GlcNAc chitin oligosaccharide sequences bound H. pylori LPSs. STL, which exhibited restricted and strong binding to 4GlcNAc tri- and pentasaccharides, differentially recognised the LPS from the strain CI-117. The chitin sequences recognised in the LPS could be internal, as no binding was detected to this LPS with WGA, known to be specific for nonreducing terminal of 4GlcNAc sequence. Analyses of the H. pylori LPSs by SDS-PAGE and Western blot with STL provided further evidence for the presence of these novel domains in the O-chain region of this LPS. H. pylori LPS microarray was also applied to analysis of two human sera. The first was from a case infected with H. pylori (H. pylori+ CI-5) and the second was from a non-infected control.The analysis revealed a higher IgG-reactivity towards H. pylori LPSs in the H. pylori+ serum, than the control serum. A specific IgG response was observed to the LPS isolated from the CI-5 strain, which caused the infection. The present thesis has contributed to extension of current knowledge on chemical structures of LPS from H. pylori clinical isolates. Furthermore, the H. pylori LPS microarray constructed enabled the study of interactions with host proteins and showed promise as a tool in serological studies of H. pyloriinfected individuals. Thus, it is anticipated that the use of these complementary approaches may contribute to a better understanding of the molecular complexity of the LPSs and their role in pathogenesis.